Social psychology and politics - Forgas, Joseph P.; Fiedler, Klaus 1951-; Crano, William D. 1942- (Sydney symposium of social psychology, 2015)
"This volume describes the role of social psychological factors in how political systems function in the 21st century. It presents new theories and evidence showing how attitudes, ideologies, communication, person perception, social cognition and group behavior constitute the foundations of political values; political perception and communication; social cognition and democracy; and identity, intergroup relations and political change. It will appeal to students and researchers in areas of social psychology, political science and public policy, and practitioners interested in the interplay of psychological processes and the functioning of political systems"--